Three‐dimensional printed microfluidic mixer/extractor for cell lysis and lipidomic profiling by matrix‐assisted laser desorption/ionization mass spectrometry. Issue 1 (23rd October 2022) - Yang, Zhengdong; Li, Bochao; Stuart, Daniel D.; Cheng, Quan
Abstract: Lipidomic profiling has been linked to the detection of cancers as dysregulation of lipid metabolism is closely associated with many disease states. Current work on chip‐based profiling has been limited and is largely hindered by issues associated with the chip's sophisticated fabrication processes. We report here the design and fabrication of a highly efficient microfluidic mixer/extractor by using three‐dimensional (3D) printing technology for on‐chip cell lysis/enrichment for lipidomic profiling with matrix‐assisted laser desorption/ionization mass spectrometry (MALDI‐MS). The platform consists of a micropillar mixer for flow‐through lysis and an on‐chip reservoir to separate phases where the lipid‐enriched layer was collected for subsequent MS analysis. The mass transfer between the two phases was simulated by a computational fluid dynamics study, and the efficiency in cell lysis in different extraction solvent systems was characterized by fluorescence microscopy. Results showed increased performance in extraction with the micropillar mixer as compared with the standard Bligh‐Dyer method. For lipid profiling of C. reinhardtii cells by MALDI‐MS, over 65 lipid species from the monogalactosyldiacylglycerol, digalactosyldiacylglycerol, diacylglyceryltrimethylhomo‐Ser, and triacylglycerol lipid families have been identified. The effect of organic solvents on extraction and lipid profiles was also investigated, and the results indicated that the extractant formula has a diverse impact on the collection of certain types of lipid species, presenting useful guidance for the system to be applied to targeted enrichment of lipids with specific cells. The microfluidic chips by the 3D printing technique reported here offer new platforms potentially for clinical lipidomics and can provide a novel avenue in disease diagnosis. Abstract : Three‐dimensional printed microfluidic mixer/extractor for on‐chip cell lysis/enrichment and lipidomic study with matrix‐assisted laser desorption/ionization mass spectrometry, showing markedly increased performance in extraction and rapid lipid profiling as a potential novel approach for cancer screening and diagnosis.